0616 Pooled Analyses From 12-week Randomized, Controlled Studies Of Solriamfetol In The Treatment Of Excessive Daytime Sleepiness In Participants With Obstructive Sleep Apnea Or Narcolepsy. (12th April 2019) - Thorpy, Michael J; Emsellem, Helene; Rosenberg, Russell; Schweitzer, Paula K; Chen, Dan; Baladi, Michelle; Babson, Kimberly; Liu, Kris; Shapiro, Colin
Abstract: Introduction: Solriamfetol, a selective dopamine and norepinephrine reuptake inhibitor, demonstrated robust wake-promoting effects in 12-week studies of excessive daytime sleepiness (EDS) associated with obstructive sleep apnea (OSA) or narcolepsy. Efficacy and safety of solriamfetol were evaluated from pooled analyses of these studies. Methods: Data from 12-week studies (2 narcolepsy, 1 OSA) were evaluated. Efficacy assessments included change from baseline to week 12 on mean sleep latency on Maintenance of Wakefulness Test (MWT), Epworth Sleepiness Scale (ESS) score, and patient-reported improvement on Patient Global Impression of Change (PGI-C) scale. Safety was also assessed. Results: Compared with participants with OSA (n=113 placebo, 343 solriamfetol [combined doses]), those with narcolepsy (n=105 placebo, 215 solriamfetol) were younger, with more females, and lower body mass index. Baseline MWT mean sleep latency and ESS scores were more severe for narcolepsy compared with OSA. Change from baseline to week 12 in MWT mean sleep latency increased in a dose-related manner compared with placebo, with least square (LS) mean differences of 2.2, 7.4, and 10.4 for 75, 150, and 300mg, respectively, for narcolepsy, and 4.7, 9.0, 11.1, and 13.0 for 37.5, 75, 150, and 300mg, respectively, for OSA. Dose-related effects were also observed for change from baseline to week 12 in ESS score, with LS mean differences of -1.8, -3.8, and -5.2 for 75, 150, and 300mg, respectively, for narcolepsy, and -2.0, -1.9, -4.5, and -4.8 for 37.5, 75, 150, and 300mg, respectively, for OSA. At week 12, the percentage of participants reported as improved on PGI-C was increased relative to placebo; results were similar between disorders. In the overall population, the most frequent (≥5%) adverse events were headache, nausea, decreased appetite, anxiety, nasopharyngitis, diarrhea, and dry mouth; the incidence was comparable in OSA and narcolepsy. Conclusion: Solriamfetol showed consistent efficacy and safety findings in both narcolepsy and OSA subjects. Solriamfetol increased wakefulness and reduced sleepiness in both groups and the adverse events profile was similar for both groups. Support (If Any): Jazz Pharmaceuticals